Evaluasi Hasil Pembelajaran Ejaan Bahasa Indonesia Sesuai EYD dan KBBI dengan Adopsi Teknologi - Chanifah Indah Ratnasari; Siti Latifah Mubasiroh (Universitas Hamzanwadi, 2022)
The average writing ability of SMPN 1 Yogyakarta students needs to be improved in terms of the Enhanced Spelling of the Indonesian Language (Indonesian: Ejaan Bahasa Indonesia yang Disempurnakan, EYD) and the Kamus Besar Bahasa Indonesia (KBBI). Therefore, the learning process is carried out with a practical approach using technology adoption (the cek-ejaan.com system and teaching videos). The purpose of this study is to evaluate the learning outcomes of Indonesian spelling according to EYD and KBBI with the adoption of technology, so that it can be determined whether the use of technology helps students improve their abilities. The subjects of this study were eighth-grade students at SMPN 1 Yogyakarta. This study is both qualitative (essay analysis) and quantitative. The data collected is in the form of pretest and posttest answers submitted by students via Google Forms. The pretest and posttest data were corrected, processed, analyzed, and visualized. The results showed that at all stages, the majority of students improved their scores (pretest < posttest), and the average posttest score was higher than the pretest average score. Therefore, it can be concluded that there is an increase in students' abilities after the learning process (even though it is fully online), and technology adoption plays an important role in this process.